Exosomes as biomarkers and therapy in type 2 diabetes mellitus and associated complications - Satyadev, Nihal; Rivera, Milagros I.; Nikolov, Nicole K.; Fakoya, Adegbenro O. J. (Frontiers in Physiology, 2023)
Type 2 diabetes mellitus (T2DM) is one of the most prevalent metabolic disorders worldwide. However, T2DM still remains underdiagnosed and undertreated resulting in poor quality of life and increased morbidity and mortality. Given this ongoing burden, researchers have attempted to locate new therapeutic targets as well as methodologies to identify the disease and its associated complications at an earlier stage. Several studies over the last few decades have identified exosomes, small extracellular vesicles that are released by cells, as pivotal contributors to the pathogenesis of T2DM and its complications. These discoveries suggest the possibility of novel detection and treatment methods. This review provides a comprehensive presentation of exosomes that hold potential as novel biomarkers and therapeutic targets. Additional focus is given to characterizing the role of exosomes in T2DM complications, including diabetic angiopathy, diabetic cardiomyopathy, diabetic nephropathy, diabetic peripheral neuropathy, diabetic retinopathy, and diabetic wound healing. This study reveals that the utilization of exosomes as diagnostic markers and therapies is a realistic possibility for both T2DM and its complications. However, the majority of the current research is limited to animal models, warranting further investigation of exosomes in clinical trials. This review represents the most extensive and up-to-date exploration of exosomes in relation to T2DM and its complications.